Implementation of ARIAS Learning Model Integrated With Constructivist Theory to Improve Student Learning Outcomes - Saminan, Saminan; Risa, Nafilah; Hamid, Tarmizi (SCAD Independent, 2017)
The low outcomes of studying physics by student at MTsN Tungkob can be influenced by several factors. One of this factor is the implementation of the method or model of learning is not suitable with the submitted materials by teachers.This study aims to find out the activities of teachers and students, the skills of teachers in managing the learning, student learning outcomes and student responses to the use of ARIAS learning model which integrated by constructivist theory of learning process. The results showed improvement of the activities both teachers and students, increasing the skills of teachers in managing the learning, and improving students’ learning outcomes. Students' response to the use of ARIAS learning model integrated by constructivist theory tend to be positive. From this study it can be concluded that the implementation of ARIAS learning model integrated by constructivist theory can improve student learning outcomes on the topic of Aircraft Simple.